PENGARUH JOB STRESS, KONFLIK PERAN, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION (STUDI KAP DI SURABAYA) - Lukmawati, Erika Yuliani (Jurnal Analisa Akuntansi dan Perpajakan, 2020)
This research was conducted to determine the influence of Job Stress, Role Conflict, Job Satisfication, and Organizational Commitment on Turnover Intention auditor at the Public Accounting Office in Surabaya. The population in this study is the auditors in KAP. This study used a random sampling method wherein this study collected 77 respondents. This study uses multiple regression linier analysis for data analysis techniques, where the results of the study show that the influence of Job Stress has a significant effect. While Role Conflict, Job Satisfication and Organizational Commitment has no significant effect